Hot Potatoes as A Learning Media to Increase the Students’ Cognitive in Japanese Language Learning - Darma, Gede Satya (English Education Department STKIP Agama Hindu Singaraja, 2022)
This current study aimed at describing the increase of students’ cognitive in Japanese Language learning in XI grade at SMK Medical Vidya Usadha using Hot Potates as a learning media. As a Quasi Experiment study, the design of this research was Nonequivalent Control Group. By involving students in XII grade as the control group and XI grade as the experiment group, the data were collected using test method, in which the data were analyzed quantitatively. The result of this research revealed the increase of students’ cognitive during the Japanese language learning in XI grade at SMK Medical Vidya Usadha. This result was confirmed and proven by the calculation of normalized gain score data. The Competence of Japanese Language showed the average score of experiment class group was more than the average score of control class group. It means that the null hypothesis (H0) was rejected.